"Death of social encounters": Investigating COVID‐19's initial impact on virtual reference services in academic libraries. (4th August 2022) - Radford, Marie L.; Costello, Laura; Montague, Kaitlin E.
Abstract: This investigation explores the initial impact of the COVID‐19 pandemic on live chat virtual reference services (VRS) in academic libraries and on user behaviors from March to December 2020 using Goffman's theoretical framework (1956, 1967, 1971). Data from 300 responses by academic librarians to two longitudinal online surveys and 28 semi‐structured interviews were quantitatively and qualitatively analyzed. Results revealed that academic librarians were well‐positioned to provide VRS as university information hubs during pandemic shutdowns. Qualitative analysis revealed that participants received gratitude for VRS help, but also experienced frustrations and angst with limited accessibility during COVID‐19. Participants reported changes including VRS volume, level of complexity, and question topics. Results reveal the range and frequency of new services with librarians striving to make personal connections with users through VRS, video consultations, video chat, and other strategies. Participants found it difficult to maintain these connections, coping through grit and mutual support when remote work became necessary. They adapted to challenges, including isolation, technology learning curves, and disrupted work routines. Librarians' responses chronicle their innovative approaches, fierce determination, emotional labor, and dedication to helping users and colleagues through this unprecedented time. Results have vital implications for the future of VRS.